pH-sensitive TRPC5 Is differentially expressed in various common skin tumors - Hopmann, Lara; Heider, Judith; Niebel, Dennis; Evert, Katja; Zeman, Florian; Hammers, Christoph M.; Ettl, Tobias; Brochhausen, Christoph; Schreml, Stephan (Biology, 2025)
Transient receptor potential classical or cation channels (TRPCs) are integral to tumor biology, particularly in maintaining Ca2+ homeostasis within cancer cells. TRPC5, a pH-sensitive member of this family, may act as a signaling molecule in the altered microenvironment of solid tumors, which are characterized by an inverted pH-gradient—with decreased extracellular and increased intracellular pH—that promotes tumor progression. This study addresses a gap in the field, as there is currently limited research on TRPC5, particularly regarding its potential role as a tumor marker. While TRPCs are known to be involved in cancer biology, the specific role of TRPC5 in solid tumors, including its potential role as a diagnostic marker, remains largely unexplored. This study is the first to examine TRPC5 expression profiles in common skin cancers, including basal cell carcinoma (BCC), squamous cell carcinoma (SCC), malignant melanoma (MM), and nevus cell nevi (NCN). Our findings reveal that the frequency of TRPC5 expression in BCC is significantly lower compared to SCC and epidermal portions of NCN and MM. These results suggest that TRPC5 could serve as an immunohistochemical marker to distinguish SCC from BCC. Additionally, this study lays the groundwork for future research into the role of TRPC5 in tumor progression and metastasis, especially since BCCs, which rarely metastasize, are predominantly negative for TRPC5.
Gesehen am 11.11.2025